Open Questions (The Hastings Center report, 2016)
A few items in this issue of the Report explore a hodge-podge of questions associated with cutting-edge genetics research. In the lead article, Charles Dupras and Vardit Ravitsky look at research into epigenetics, which refers to molecular mechanisms that affect how genes are expressed. As Dupras and Ravitsky explain, research into epigenetics might turn out to be useful for developing environmental and social strategies for improving public health, but it might also end up leading to clinical tools—tools that work at the “molecular” instead of the social level and that target individuals rather than the collective public. Dupras and Ravitsky plainly hope to see a good effort to develop environmental and social strategies, and they fear that funding and interest will go mostly the other way, toward ever more “molecular” interventions. That trend in funding and interest is reflected, to some degree, in the second article, in which Oscar Zarate and colleagues explore how the Personal Genome Project, an endeavor launched at Harvard University to collect and share personal genetic and health information in order to facilitate research, is perceived by the people who consent to be part of it. Questions about open consent and subjects' role in fostering research recur in several shorter contributions to this issue. In the lead essay, Carl Elliott reflects on how and why the language used to describe research has been updated (“subjects” giving way to “participants” and “experimentation” to “research”) and suggests that the changes reflect an effort to deflect concerns about the treatment of subjects.